RELATIONSHIP BETWEEN THE PERIODONTITIS AND THE CAUSED ILLNESSES FOR ATHEROSCLEROSIS. BIBLIOGRAPHIC REVIEW - López Ilisástigui, Alina (2016)
The atherosclerosis and the periodontal illness have a high prevalence in the world. It is raised that events produced by the first one, cause numerous annual deaths, as well as inability in the population. The periodontal illness is cause of tooth loss it, mainly in adult population, besides having a high prevalence and it is presented in all countries with more or smaller affectation. Apparently these illnesses only are resembled each for this high prevalence, however, in the last years many authors have outlined the influence that the periodontal illness has on the atherosclerotics events and that it can be considered as factor of risk of the same ones.